Screening race in American nontheatrical film - Field, Allyson Nadia 1976-; Gordon, Marsha 1971- (Duke University Press, 2019)
"Although overlooked by most narratives of American cinema history, films made for purposes outside of theatrical entertainment dominated twentieth-century motion picture production. This volume adds to the growing study of nontheatrical films by focusing on the ways filmmakers developed and audiences encountered ideas about race, identity, politics, and community outside the borders of theatrical cinema. The contributors to this book examine the place and role of race in educational films, home movies, industry and government films, anthropological films, and church films as well as other forms of nontheatrical filmmaking. From filmic depictions of Native Americans and films by 1920s African American religious leaders to a government educational film about the unequal treatment of Latin American immigrants, these films portrayed--for various purposes and intentions--the lives of those who were mostly excluded from the commercial films being produced in Hollywood. This volume is more than an examination of a broad swath of neglected twentieth-century filmmaking; it is a reevaluation of basic assumptions about American film culture and the place of race within it."--
Keywords: Cinéma en éducation; Films d'amateurs; Films ethnographiques; Minorités au cinéma; Noirs américains au cinéma; Race au cinéma; 20.10 art and society: general; 24.32 history of film art; African Americans in motion pictures; Amateur films; Amateurfilm; Bildung; Ethnographic films; Ethnologie; Minorities in motion pictures; Motion pictures in education; Nationale Minderheit; Race awareness in motion pictures; Race in motion pictures; Schwarze; Amateur films -- United States; Ethnographic films -- United States; Motion pictures in education -- United States; USA; United States; Electronic books; Aufsatzsammlung